Szoboravatás - Mózes, Péter (Gerundium, 2016)
INAUGURATION OF A STATUE OF DR. GYULA ELISCHER (1875–1939) IN THE SCULPTURE GARDEN OF DEBRECEN UNIVERSITY’S CAMPUS. he brief text highlights the inauguration, on November 8, 2014, of a bust of Gyula Elischer of hurzóbánya on the campus of the University of Debrecen. he text ofers a description of the life career of the world-famous radiologist professor, Hungary’s irst radiographer, his professional achievements and printed publications. he text also underscores the fact that Professor Elischer – like many other doctors of the heroic age of radiology – sacriiced his life in the service of science and of his fellow human beings.